Examining the Literature on Industry 4.0 and Society 5.0's Prospects and Pitfalls - LEI RONGMING (International Journal of Multidisciplinary Research and Studies, 2023)
As a result of advancements in operational efficiency and the creation and implementation of new business models, services, and products, the manufacturing and production systems of the modern period have been dubbed "Industry 4.0." The primary objective for Industry 4.0 was to enhance the manufacturing systems' eco-friendliness and productivity. As a corollary, system enhancements were prioritized via both digitization and digitalization. However, the focus of the present technological progress is more on systems and machines than on humans. As a result, several nations have already started coordinating efforts to bring about Industry 5.0, a term referring to the design and development of human-centric technologies, systems, and services. Industry 5.0 will have far-reaching effects, resulting in a new social order known as Society 5.0. Tools and technologies developed within the context of Industry 4.0 will be designed with social and human factors in mind. For this reason, the next technological phase, dubbed Industry 5.0 and a subset of Society 5.0, will prioritize human well-being and environmental sustainability. Human-centered, resilient, and sustainable design will be at the forefront of Industry 5.0, which will expand upon the groundwork built by the previous generation. Therefore, the authors of this study want to give sufficient justification for thinking about Industry 5.0 as a framework for allowing industry and developing society trends and requirements to coexist via a critical literature assessment. Additionally, this study contributes by laying out a plan for how to go from the current Industry 4.0 to the future Society 5.0.